THE EFFECT OF BLENDED LEARNING AND INDEPENDENT LEARNING ON LEARNING OUTCOMES OF ISLAMIC RELIGIOUS EDUCATION FOR TANJUNG PURA JUNIOR HIGH SCHOOL STUDENTS - Supriadi Supriadi; Sapri Sapri; Rahmah Fithriani (TA'DIB: JURNAL PENDIDIKAN ISLAM, 2022)
The purpose of this study was to determine the effect of Blended Learning, independent learning and the influence of Blended Learning and independent student learning together on the learning outcomes of Islamic Religious Education at Tanjung Pura Langkat Middle School. This type of research is a quantitative study with a population of 244 people, so that the sample taken is 150 people. The results of the study revealed that there was a positive and significant influence between Blended Learning on Islamic Religious Education learning outcomes where Blended Learning had an effect of 6.1% on PAI learning outcomes and the remaining 93.9% was determined by other factors. The independence of learning has an influence on the learning outcomes of Islamic Religious Education by 10.3% and the remaining 89.7% is determined by other factors. Meanwhile, the learning outcomes of Islamic Religious Education, Blended Learning and independent learning have an influence of 16.5% and the remaining 83.5% is determined by other factors.